Penalaran Hukum Hakim Dalam Memberikan Izin Poligami (Studi Putusan Pengadilan Agama Bukittinggi Nomor 575/Pdt.G/2024/Pa.Bkt) - Rifan Saputra; Nurus Shalihin; Elfia Elfia; Aulia Rahmat (IDRIS Darulfunun Institute, 2026)
This study aims to analyze the legal reasoning employed by judges in granting permission for polygamy in the Decision of the Bukittinggi Religious Court Number 575/Pdt.G/2024/PA.Bkt. The research focuses on the judges' interpretation of the legal provisions governing polygamy, their considerations in assessing the first wife's consent, the applicant's financial capability, and personal character, as well as the forms of rechtsvinding (judicial law-finding) and legal reasoning applied in the decision-making process. This research adopts a qualitative approach using a case study design. Primary data were obtained through in-depth interviews with the judge who examined and decided the case, while secondary data were collected from the court decision, statutory regulations, the Compilation of Islamic Law (Kompilasi Hukum Islam), and relevant scholarly literature. Data were collected through interviews, document analysis, and library research, and analyzed using the interactive model of Miles, Huberman, and Saldaña, which consists of data condensation, data display, and conclusion drawing. The findings reveal that the judges' legal reasoning was not limited to the literal application of statutory provisions but involved systematic, teleological, and sociological interpretation by considering the facts established during the trial, the principles of justice, public benefit (maslahah), and the protection of wives and children. The first wife's consent was not regarded as the sole basis for granting permission for polygamy but was evaluated alongside the applicant's financial capacity, responsibility, and personal integrity. Financial capability was assessed contextually without applying a fixed income threshold, while the applicant's character was evaluated through evidence concerning moral conduct, responsibility, and social behavior. The study concludes that the judges' reasoning reflects the implementation of rechtsvinding by integrating legal certainty, justice, and expediency to produce decisions that prioritize family protection and substantive justice.